2015
DOI: 10.1096/fj.15-279802
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin D: an Mφ‐derived factor mediating increased endothelial cell permeability with implications for alteration of the blood‐retinal barrier in diabetic retinopathy

Abstract: Inflammation plays an important role in the pathogenesis of diabetic retinopathy (DR). We have previously reported increased monocyte (Mono) trafficking into the retinas of diabetic animals. In this study, we have examined the effect of activated Monos on retinal endothelial cells (ECs). The U937 Mf-conditioned medium (CM) significantly decreased the transendothelial resistance of EC monolayers as measured by electric cellsubstrate impedance sensing (P = 0.007). The CM was fractioned, and the effective fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 61 publications
0
18
0
Order By: Relevance
“…We have previously shown that the addition of M6P with CD stabilizes endothelial resistance (12). In the current study, we have shown the direct interaction of the ligand and the receptor using an ELISA‐based method (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously shown that the addition of M6P with CD stabilizes endothelial resistance (12). In the current study, we have shown the direct interaction of the ligand and the receptor using an ELISA‐based method (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, we reported the effect of the macrophage‐derived factor, CD, on the mediation of increased endothelial cell permeability in the retinas of diabetic mice (12). Here, we have demonstrated the effect of pro‐CD on the endothelial–pericyte interaction via the modulation of PDGFRβ, N‐Cad, and Ang2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Monickaraj et al [72] reported that patients suffering from manifest diabetic macular edema, a consequence of diabetic retinopathy, had elevated cathepsin D levels in their serum. The protease caused mechanical disruption of the endothelial barrier through increased RhoA-ROCK-dependent contractility in human retinal endothelial cells.…”
Section: Diabetic Retinopathymentioning
confidence: 99%